The Impact of Remittance on Poverty and Inequality: A Micro-Simulation Study for Nepal - ACHARYA, Chakra P; LEON-GONZALEZ, Roberto (Asian Journal of Empirical Research, 2013)
Using nationally representative panel data from Nepal, we estimate a household consumption function and simulate the impacts of remittance on poverty and inequality. We study how these impacts vary with regional maturity of migration process and country-source of remittance. The results show that remittance has positive impacts on reduction of all the incidence, depth and severity of poverty; the magnitude of impact increases with the depth and severity of poverty and it is larger in the second round of the survey. The region-wise simulations show that the remittance has larger impacts on poverty reduction in the regions that have higher levels of migration. The effect on income equality is adverse but it is smaller in the second round. These findings suggest that the impacts largely depend on the maturity of migration process as well as the participation of lower quintiles of society in the process. For instance, the remittance from India — the oldest and most convenient destination, which is on average much lower than from other countries, has not only the largest impacts on poverty reduction but also has favourable impacts on income equality.